Physical Medicine and Rehabilitation of Knee Osteoarthritis Grade 3-4 with Valgus Deformity - Annisa Nadia Utami; Juatmadja, Bastianus Alfian (Surabaya Physical Medicine and Rehabilitation Journal, 2025)
Introduction: Osteoarthritis is an arthritic disease caused by joint cartilage damage that affects an estimated 302 million people worldwide. Factors that increase the risk of OA include being a woman, aged over 45, obesity, bone deformities, joint injuries, and repetitive strain on specific joints. Osteoarthritis is the leading cause of disability among older adults and needs a high health care and rehabilitation cost. The primary focus of treatment is symptom management and maintenance or restoration of functional capacity. The PMR programs include therapeutic exercises, modality uses, education and lifestyle modification (knee joint conservation). We aimed to determine the impact of PMR program combined with pharmacological therapy on 3rd-4th grade OA patients.  Methods: Case report of a woman, aged 62 years, diagnosed with right knee OA grade 3-4 with valgus deformity. Subject has chronic and progressive knee pain by visual analog scale (VAS) was 4-5, limited range of movement (ROM) in the right knee, and low back pain. The patient performed medical rehabilitation program combined with pharmacological therapy at Mitra Husada Pringsewu Hospital for 6 weeks and it was evaluated.  Results: Patient in comparison before and after treatment, pain was reduced from VAS score 4-5 to 3-4, ROM from extentiont-flexion angle 15-90o to 5-110o, Q angle remained the same, and The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) score was decreased from 11-5-34 to 9-3-30.  Conclusion: A nonpharmacological and pharmacological therapy combination in medical rehabilitation programs  is needed to reduce pain, improve ROM, and improve the patient's quaity of life.